An assessment of human carnivore conflict in the Kalahari region of Botswana - Klein, Rebecca Ann (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2014)
Human wildlife conflict is a considerable conservation challenge that threatens many carnivore species worldwide and is a result of complex socio-economic and ecological processes. An understanding of the drivers of conflict is essential for any efforts to achieve coexistence. This study investigated the levels of conflict, livestock management and tolerance amongst the farming communities of the Southern and Western Kalahari in Botswana. A questionnaire survey was completed with 310 farmers throughout the region. The majority of respondents regarded coexisting with carnivores as a challenge, with losses due to depredation perceived as the greatest problem facing farmers. Conflict was widespread throughout the study area, with some spatial variations for certain species. Cattle management levels were low and while smallstock management was better, the use of improved levels of management could reduce current levels of conflict. Tolerance levels were generally low with few respondents seeing the benefits of coexistence with carnivore species. The results indicated that farm type, gender, education level, source of income, livestock numbers, location and land use all have an effect on perceived conflict and tolerance levels and strongly interact with each other. In general cattleposts were characterised by higher proportions of females, lower education levels, more benefits derived from wildlife and veld products and fewer livestock than fenced ranches. They also experienced more conflict, carried out more management and had better tolerance levels. It could be that closer connections to the land and deriving benefits from natural resources resulted in more tolerance and this is certainly worth further investigation. An improvement in the use of effective methods of livestock management, targeted environmental education programs to develop a greater awareness for the conservation value of carnivores and a diversification of livelihoods to include benefits from natural resources have the potential to reduce conflict and improve tolerance in the Kalahari region.
Keywords: Carnivores -- Botswana; Carnivores -- Effect of human beings on -- Botswana; Human-animal relationships; Predatory animals -- Control -- Botswana; Wildlife depredation -- Botswana